1992
DOI: 10.1007/bf01923447
|View full text |Cite
|
Sign up to set email alerts
|

Sleep in an Amazonian manatee,Trichechus inunguis

Abstract: For the first time, sleep was studied in a representative of the order of Sirenia. Slow wave sleep occupied 27%, and paradoxical sleep 1% of the total recording time in the Amazonian manatee. Trichechus inunguis. The circadian rhythmicity of sleep was pronounced. During the sleep period, the manatee woke up for a short time for each respiratory act. Interhemispheric asynchrony of the electrocortical slow wave activity was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 1 publication
0
24
0
Order By: Relevance
“…Moss [1982] reported that wild African elephants, L. africana, sleep a total of 3-5 h at night, whereas captive Asian elephants, E. maximus, slept for approximately 4-6.5 h [Tobler, 1992;Wilson et al, 2006]. An electrophysiological study on an Amazonian manatee, T. inungius , revealed that this animal spent approximately 6.5 h (27%) in SWS and 14.4 min (1%) in REM sleep over a 24-hour period and that 25% of SWS was occupied by interhemispheric asymmetry [Mukhametov et al, 1992]; however, it must be noted that the TST reported was based on the study of a single animal and the recording of sleep was done directly after surgery, thus the TST obtained may not be representative of this species. As for the insectivoran-like afrotheres, TST in the tenrecs has been reported to be 15.6 h, with SWS contributing 13.26 h and REM 2.34 h [Campbell and Tobler, 1984;Elgar et al, 1988;Snyder et al, 1972].…”
Section: Comparison To Sleep In Other Afrotheria Xenarthra and Othermentioning
confidence: 99%
See 1 more Smart Citation
“…Moss [1982] reported that wild African elephants, L. africana, sleep a total of 3-5 h at night, whereas captive Asian elephants, E. maximus, slept for approximately 4-6.5 h [Tobler, 1992;Wilson et al, 2006]. An electrophysiological study on an Amazonian manatee, T. inungius , revealed that this animal spent approximately 6.5 h (27%) in SWS and 14.4 min (1%) in REM sleep over a 24-hour period and that 25% of SWS was occupied by interhemispheric asymmetry [Mukhametov et al, 1992]; however, it must be noted that the TST reported was based on the study of a single animal and the recording of sleep was done directly after surgery, thus the TST obtained may not be representative of this species. As for the insectivoran-like afrotheres, TST in the tenrecs has been reported to be 15.6 h, with SWS contributing 13.26 h and REM 2.34 h [Campbell and Tobler, 1984;Elgar et al, 1988;Snyder et al, 1972].…”
Section: Comparison To Sleep In Other Afrotheria Xenarthra and Othermentioning
confidence: 99%
“…For members of the Afrotheria, sleep has been recorded behaviorally in captive Asian, Elephas maximus, and African elephants, Loxodonta africana, with TST in these animals being 4-6.5 and 3.3 h, respectively [Kurt, 1960;Tobler, 1992]. Electroencephalogram (EEG) recordings of a fully aquatic Amazonian manatee, Trichechus inungius, showed that this animal spent 6.48 h (27%) of the recorded time in SWS, which could be unihemispheric in nature, and 14.4 min (1%) in paradoxical or REM sleep [Mukhametov et al, 1992]; however, the study was performed on a single animal and the sleep recording commenced directly after surgery and lasted only a few days. Within the Hyracoidea, Snyder [1974] reports a TST of 4.9 h for Procavia johnstoni (rock hyrax) , 5.7 h for Heterohyrax brucei (bush hyrax) and 4.9 h for Dendrohyrax validus (tree hyrax); however, only an abstract has been published for the aforementioned study and detailed evidence has not been provided to support the reported data.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to Cetaceans, the degree of IA is usually less pronounced in eared seals and least pronounced in birds. In Cetaceans, deep SWS virtually never occurs simultaneously in both hemispheres, whereas eared seals, manatees and birds frequently show deep SWS in both hemispheres [Ball et al, 1988;Lyamin and Chetyrbok, 1992;Mukhametov et al, 1992]. Although mammals and birds exhibit two types of sleep (i.e., SWS and rapid-eye-movement, REM, sleep), only SWS occurs unihemispherically.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they noted that the [58] , though an earlier study by Shurley et al (in 1969) reported episodes of REM sleep in the pilot whale [59] . In all subsequent physiological studies, however, it was confirmed that REM sleep is absent from the Cetacea bottle nose dolphin [60] , black sea porpoise [61] , amazon river dolphin [62] and beluga whale [63] , while in the amazon manatee (Sirenia), only a few episodes of REM sleep were recorded [64] .…”
Section: Mukhametov and His Team (In 1975) Recorded Eeg Inmentioning
confidence: 95%
“…In fact, it has been suggested that sleep in fur seals defies the principle of homeostatic regulation, since no rebound of lost REM is seen when it returns to land after staying several weeks in water [42] . (dolphin and white whale: 0%; manatee: 1%) [64,65] . Semi- as disk-over water, multiple or single platform, and wiremesh grid platform in which water is used as the surrounding medium [66][67][68][69] .…”
Section: Do Aquatic Conditions Disfavor Rem Sleep Continuity?mentioning
confidence: 99%